The risk associated with strategic decisions: is it a marketing issue?. Issue 1 (14th January 2019) - Settembre-Blundo, Davide; Fernández del Hoyo, Alfonso Pedro; García-Muiña, Fernando Enrique
Abstract : Purpose: The purpose of this paper is to analyze the strategic management of risks in companies from a marketing management perspective and to provide some guidance for management practice. Design/methodology/approach: This paper presents the authors' viewpoint, and it conceptualizes a new approach to risk management. Findings: The conceptual discussion has opened up a possible new way for enterprises, especially SMEs, to start taking a strategic approach to risk. Originality/value: This paper would like to contribute to the current debate on the role of marketing function in managerial practice beyond the classic four Ps.